Urban and Rural Differences in Cancer Treatment Disruption Among Patients With COVID‐19: An Analysis of the US ASCO COVID‐19 in Oncology Registry - Yu Chen Lin; Kea Turner; Oliver T. Nguyen; Emma Hume; Marlene Camacho‐Rivera; Jessica Y. Islam (Cancer Medicine)
ABSTRACT Introduction Cancer patients in rural areas experience greater barriers to treatment access compared with patients in urban areas. There is limited research on how the COVID‐19 pandemic affected cancer treatment delivery for rural patients who were also diagnosed with COVID‐19. This study has two objectives: to assess (1) the urban–rural differences in cancer care and (2) the predictors of cancer treatment delay or discontinuation (TDD) among patients diagnosed with COVID‐19. Methods We used data from the American Society of Clinical Oncology Survey on COVID‐19 in Oncology Registry (March 2020–September 2022), which included cancer patients with test‐confirmed SARS‐CoV‐2 infection (N = 3797). Data included patient sociodemographic characteristics, COVID‐19 diagnosis information, cancer clinical characteristics, and changes to cancer treatment. Cancer TDD was defined as any scheduled treatment by more than 2 weeks. Rurality was examined through both patient residence and oncology practice. We computed adjusted prevalence ratios (aPRs) using multivariable Poisson regressions to assess predictors of cancer TDD in urban and rural areas. Results During the study period, 44.1% of patients with COVID‐19 experienced either cancer treatment delay or discontinuation and 5.7% experienced cancer treatment discontinuation. Controlling for other factors, receiving care in a rural oncology practice was associated with cancer TDD (aPR: 1.25, 95% CI: 1.01–1.55). Differences in cancer TDD were not found across rurality of patient residence. Among rural patients (N = 582), Hispanic/Latinx cancer patients had greater prevalence of cancer TDD (aPR: 1.55, 95% CI: 1.04–2.33) compared with non‐Hispanic White cancer patients. Conclusion Our findings can be used to inform programs and policies to minimize the impact of future public health emergencies on cancer care delivery in rural areas. Additional research is needed to explore potential differences in cancer care delivery across urban and rural oncology practices and patients.